Passive acoustic detection of Shark Bay dugons (Dugon dugon) - Parsons, Miles; Holley, D.; McCauley, Robert (Acoustical Society of Australia, 2012)
Shark Bay, Western Australia is home to the one of the largest populations of dugongs (Dugong dugon) in the world. During winter months the dugongs predominantly reside in warmer western and northern waters of the gulfs, moving south between September and October as the shallower, more southern waters warm. Two underwater noise loggers, sampling at 12 kHz were deployed off Guichenault Point and Skipjack Point in Shark Bay's eastern gulf between the 16th September and 21st October, 2011 to record sounds produced in waters between 4 and 15 m depth. Speculated dugong calls were recorded sporadically throughout the deployment. However, on the 4th and 5th October several hours of biological 'short chirps' were recorded by the Guichenault Point logger. These calls displayed similar acoustic characteristics to chirps in previous reports, though of much shorter duration. Maximum received levels of 134 dB re 1µPa (±5.2 s.d., max = 143.3, min = 123.8) and maximum received sound exposure levels 114 dB re 1µPa2.s (±5.3 s.d., max = 121.9, min = 103.4) were observed from 40 calls. Mean spectral peak frequency of 333 Hz (±316, max = 3610, min = 1957) with a 6 dB down bandwidth of 2746 Hz (±1685, max = 5250, min = 731) over a duration of 0.2 s (±0.17, max = 0.7, min = 0.004) were observed over the group of calls. The calls were also split into 3 smaller types and the acoustic characteristics of these speculated dugong calls are discussed.